An LCA study comparing e-books read on an Apple Air iPad to printed books in South Africa - Naicker, Vinesh (Energy Research Centre, 2017)
A number of studies assessing the environmental impacts of print media systems in comparison to digital media systems offering the same services have been conducted in United States of America (USA) or Sweden. The most notable are studies done by Kozak (2003), Gard & Keoleian (2003), Enroth (2009), Moberg et al. (2011) and Achachlouei et al. (2013). However, no studies have been conducted in South Africa. The main purpose of this study was to compare environmental impacts and cumulative energy demand of electronic books (e-books)read from a Tablet personal computer (PC) or Apple Air iPad, the digital system, with the equivalent printed paper books (print system) in South Africa, and establish which of two systems has less of an environmental and energy demand impact. The study was aimed at creating awareness amongst consumers and producers about the environmental and energy impacts of both systems. The study also included scenarios which investigated the effect that changing the energy mix as planned in the 2010 Integrated Resource Plan (IRP) has on the environmental impacts and cumulative energy demand of both systems, and the effect of multiple users per system. The initial hypothesis of this study was that reading 21 e-books from a Tablet PC would have a lower environmental impact and cumulative energy demand than reading 21 printed books. The time period of the study is four years, the length of time for completing a commerce university degree. During this period each learner will purchase 21 books, either in the form of printed paper books or as e-books that can be read using a Tablet PC.